2010
DOI: 10.1002/marc.201000490
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Micro‐ and Nano‐Capsules

Abstract: In this work, we introduce anisotropically shaped, ultrathin micro- and nano-capsules fabricated by layer-by-layer approach. The original cubic and tetrahedral shapes of the template particles were replicated to produce hollow capsules with well-defined edges. Introducing tannic acid as a component of LbL shells resulted in enhanced chemical stability of these hollow polymer structures under a wide pH range due to high pK(a) value. Computational studies demonstrated increased mechanical stability of the anisot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 43 publications
2
63
0
Order By: Relevance
“…16,18,19 Furthermore, the non-spherical shape of the capsules oen lose aer removing the templates due to high residual stresses or osmotic pressures. 16,18,19 In terms of such challenges, PDA coating is valuable due to its capability to form a conformal coating layer on particulate templates with any kinds of shapes. 5,6,[9][10][11][12] Even so, PDA capsules with an anisotropic shape have barely been reported.…”
Section: 17mentioning
confidence: 99%
“…16,18,19 Furthermore, the non-spherical shape of the capsules oen lose aer removing the templates due to high residual stresses or osmotic pressures. 16,18,19 In terms of such challenges, PDA coating is valuable due to its capability to form a conformal coating layer on particulate templates with any kinds of shapes. 5,6,[9][10][11][12] Even so, PDA capsules with an anisotropic shape have barely been reported.…”
Section: 17mentioning
confidence: 99%
“…Thus, future trends in particle-directed drug delivery are toward novel methods of synthesis and elaboration of anisotropic particles which in specific cases resemble natural vehicles like bacteria [117]. Not only particles of certain shapes can be used as delivery system, but also capsules templated on specifically shaped particles would be beneficial to certain applications [118,119]. The flexibility of polyelectrolytes molecules allows reproducing a number of capsule shapes after decomposition of the initial solid cores [119][120][121].…”
Section: Anisotropic Capsules and Anisotropic Carriersmentioning
confidence: 99%
“…Not only particles of certain shapes can be used as delivery system, but also capsules templated on specifically shaped particles would be beneficial to certain applications [118,119]. The flexibility of polyelectrolytes molecules allows reproducing a number of capsule shapes after decomposition of the initial solid cores [119][120][121]. Shchepelina et al compared the morphology, mechanical properties, and permeability of hydrogen-bonded layer-by-layer (LbL) microcapsule shells assembled on squared cadmium carbonate particles against the same shells assembled on spherical silica.…”
Section: Anisotropic Capsules and Anisotropic Carriersmentioning
confidence: 99%
“…[26], [27] The flexibility of polyelectrolytes allows keeping different shapes of the formed multilayer capsules after decomposition of the sacrificial solid templates. [28] Shchepelina et al compared morphology, mechanical properties, and permeability of hydrogen-bonded LbL microcapsule shells assembled on square cadmium carbonate against the same shells assembled on spherical silica. [23] The patterned template-assisted assembly of the cubic micro-particles driven by the competing capillary, Coulombic, and van der Waals forces in comparison with the traditional spherical colloidal microparticles had been studied by Lisunova et al [29] Doxorubicin cubes have been identified as effective carriers of doxorubicin in cells, [30] while cubic shape has been reported to be effective for the interaction of LbL polymeric particles with breast cancer cells.…”
Section: Anisotropic Shapesmentioning
confidence: 99%